Rancang Bangun Sistem Manajemen Rantai Pasok (Supply Chain Management) Berbasis Website Menggunakan Metode Agile Scrum untuk Optimalisasi Operasional pada PT. Bintang Plastik Sempurna - Sabrina Luna Apsari Faizah; Afiani Agus Abdilla; Fajar; Fariza Arlistiana (CV. Shofanah Media Berkah, 2026)
PT. Bintang Plastik Sempurna is a manufacturing company operating in the plastic injection sector, with a production process involving the use of milling, welding, and polishing machines. Currently, operational data management, which encompasses raw material inputs, production process monitoring, production sales recording, as well as supplier and customer data management, is still conducted conventionally using Microsoft Excel. This manual system leads to several constraints, including the risk of data duplication, the absence of real-time stock monitoring, and delays in compiling periodic reports. This study aims to design and implement an integrated web-based Supply Chain Management (SCM) system to optimize operational efficiency. The system development method applied is Agile Scrum, developed iteratively through the stages of product backlog, sprint planning, sprint execution, and sprint review. This web-based system is integrated with a MySQL database and features binary Excel synchronization via Bulk Insert commands alongside an automated PDF generator engine for internal memos and delivery notes. Based on functional evaluation using the Black Box Testing method, all features within the application are declared to operate according to expectations. The implementation of this system has proven successful in automating data processing from upstream to downstream, minimizing human errors, and enhancing the company's overall operational productivity.